Bootstrap panel Granger-causality between government budget and external deficits for the EU - Rault, Christophe (2022)
We investigate the existence of Granger-causality between current account and government budget balances over the period 1970-2007, for different EU and OECD country groupings. We use a panel-data approach based on SUR systems and Wald tests with country specific bootstrap critical values. Our results show a causal relation from budget deficits to current account deficits for several EU countries: Bulgaria, Czech Republic, Estonia, Finland, France, Italy, Hungary, Lithuania, Poland, and Slovakia, along the lines of the so-called twin-deficit relationship. Considering the effective real exchange rate in the SUR system does not substantially alter the results.